DNA-based biosensor platforms for the detection of TP53 mutation - Altintas, Zeynep; Tothill, Ibtisam E. (Elsevier Science B.V., Amsterdam., 2012)
A DNA-based assay for the detection of one-point mutation in TP53 gene, responsible for lung cancer, was developed using a surface plasmon resonance (SPR) and a quartz crystal microbalance (QCM) biosensor systems. Amine coupling was employed for the immobilization of NeutrAvidin on thiol-derivatized surface to capture the biotinylated target sequence. Two targets sequences and one control DNA sequence were investigated including, a fully complementary (30 mer), one-point mutation and a non-complimentary DNA using hybridization with a detection probe strand (27 mer). The most appropriate surface coating was also examined for both sensor platforms with hybridization and single nucleotide polymorphism (SNP) detection efficiency were then compare. A 0.03-2 μM concentration range of detection probe was detected using the SPR and QCM sensors on wild and mutant type target surfaces. The linear regression analysis was performed for both sensors resulting in a R 2 value for the SPR assay of 0.985 and 0.993 for perfect and mismatch reaction and of 0.978 and 0.976 for the QCM assay, respectively. The obtained results demonstrate that the used approach represents a very promising future method for the detection of one-point mutation in genetic-based health problem with highly sensitive, specific, and real-time analysis